THE SAGA OF POTTALI KALPANA - PVNR. Prasad; P.H.C. Murthy (International Journal of Applied Ayurved Research, 2016)
Pottali is one of the Parada yogas with Mercury and Sulphur being the principle ingredients and is grouped under Moorchita Parada Yoga. It is a specialized pharmaceutical technique invented with the vision of compact in size, Convenience in preservation and ease in trans-portation. It has wide therapeutic applications as well as methods of preparation. The word Pottali has been used in Ayurvedic classical books for different purposes. Pottali, as a struc-ture keeps resemblance with a pouch having some herbal or other drugs in it. Various Pottali kalpas have been mentioned and described in Rasa Shastra literature with variation in their shape, size, appearance, ingredients, method of preparation and therapeutic indications. Pottali Rasayan is a milestone in the history of Ayurvedic Emergency and Critical Care.